σ(B) and σ(L) Contribute to Listeria monocytogenes 10403S Response to the Antimicrobial Peptides SdpC and Nisin - Palmer, M. Elizabeth (Mary Ann Liebert, Inc., 2009)
The ability of the foodborne pathogen Listeria monocytogenes to survive antimicrobial treatments is a public health concern; therefore, this study was designed to investigate genetic mechanisms contributing to antimicrobial response in L. monocytogenes. In previous studies, the putative bacteriocin immunity gene lmo2570 was predicted to be regulated by the stress responsive alternative sigma factor, σ(B). As the alternative sigma factor σ(L) controls expression of genes important for resistance to some antimicrobial peptides, we hypothesized roles for lmo2570, σ(B), and σ(L) in L. monocytogenes antimicrobial response. Results from phenotypic characterization of a L. monocytogenes lmo2570 null mutant suggested that this gene does not contribute to resistance to nisin or to SdpC, an antimicrobial peptide produced by some strains of Bacillus subtilis. While lmo2570 transcript levels were confirmed to be σ(B) dependent, they were σ(L) independent and were not affected by the presence of nisin under the conditions used in this study. In spot-on-lawn assays with the SdpC-producing B. subtilis EG351, the L. monocytogenes ΔsigB, ΔsigL, and ΔsigB/ΔsigL strains all showed increased sensitivity to SdpC, indicating that both σ(B) and σ(L) regulate genes contributing to SdpC resistance. Nisin survival assays showed that σ(B) and σ(L) both affect L. monocytogenes sensitivity to nisin in broth survival assays; that is, a sigB null mutant is more resistant than the parent strain to nisin, while a sigB null mutation in ΔsigL background leads to reduced nisin resistance. In summary, while the σ(B)-dependent lmo2570 does not contribute to resistance of L. monocytogenes to nisin or SdpC, both σ(B) and σ(L) contribute to the L. monocytogenes antimicrobial response.